Portable compression devices in total joint arthroplasty: poor outpatient compliance - Dietz, Matthew J. (Arthroplast Today, 2020)
BACKGROUND: Aspirin and mechanical compression devices are approved means of venous thromboembolism (VTE) prophylaxis after total joint arthroplasty. Prior studies of mechanical compression pumps after joint arthroplasty have been limited to the inpatient setting. The purpose of this study was to evaluate outpatient compliance and utilization factors in a rural population after elective hip or knee arthroplasty. METHODS: Utilization for portable pneumatic compression pumps after joint arthroplasty was prospectively recorded (hours). Compliance was defined as the recommended 20 hours per day. A questionnaire 2 weeks postoperatively assessed factors that may contribute to noncompliance. Patients were followed up for 90 days postoperatively to record VTE events. RESULTS: Data were collected for 115 joint arthroplasty patients (50 hips, 65 knees). Postdischarge day one had the highest average usage at 13.2 hours/day (66.0%, range 0%-100%), but this number fell to 4.8 hours/day (24.0, range 0%-100%) by day 14. Patient compliance (>20 hours use/day) was highest on postdischarge day one at 40 patients (34.7%). By postdischarge day 14, patient compliance fell to 17 patients (14.8%). Difficulty using the pumps (P = .027) and pump-associated heat (P = .009) were significantly associated with patient compliance. A deep vein thrombosis and nonfatal pulmonary embolism were recorded in 2 separate patients. CONCLUSIONS: This study demonstrated poor outpatient compliance with portable pneumatic compression devices. Poor compliance was related to pump heat and difficulty with pump use. Even with poor compliance, a low incidence of VTE events was observed.